Práticas de linguagem na sala de aula: caminho para a formação da competência comunicativa - Rodrigues Júnior, Hélio (2011)
Portuguese PCN (Brazil, 1998) for elementary school were expressively a breakthrough in the teaching of writing production, appropriating textual genres as a way to bring the educational practices of language in the classroom. However, methodological proposals have not the teaching of these situations in which the tongue is placed into operation, i.e. not signal paths to the act of professor, generating numerous doubts as to how to think the teaching of genres and how to direct them in a manner satisfactory to the training of student's communicative competence. Arises from the main objective of this work connected to the contribution to the teaching of Portuguese language by means of a written production strategy of a textual genre, seated in epilinguagem activities, precisely, in rewritten, guided by aspects of Interactionism sociodiscursive, Linguistics education, Textual linguistics and Textual analysis of the speech. Two groups were formed, one that he wrote without any interference from the researcher and the other which was accompanied by researcher while teaching sequences were applied. We then compared the results with the purpose to prove our hypothesis that students who have had an approach of teaching by practices of language, in the focus of textual and discursive analyses on interaction activityoriented textual genres presented greater competence in the use of the language. We found that our hypothesis is true, since the rewrite of the text, together with a control list, didactic instrument used by the Geneva Group, allows the student, in textual refacção, take ownership of the genres of text, allowing you to tailor your speech to a particular communication situation. We propose and apply conscious intervention, revealed as an important tool for teaching and learning of writing in the school production